The association between lung cancer stigma and race: A descriptive correlational study - Karen Kane McDonnell Associate Professor; Lisa A. Webb New Knowledge, Improvement, and Innovation Coordinator; Swann A. Adams Professor; Tisha M. Felder Associate Professor; Rachel E. Davis Associate Professor (Wiley, 2022)
Abstract Background Stigma is a formidable burden for survivors of lung cancer that can reduce the quality of life (QOL), resulting in physical, social and psychological challenges. This study investigates associations between stigma and depression, QOL and demographic and health‐related characteristics, including race. Design An adapted conceptual model derived from the Cataldo Lung Cancer Stigma Scale guided this descriptive correlation study assessing stigma in African American and Caucasian survivors of lung cancer. Self‐reported, written surveys measuring depression, QOL, lung cancer stigma and demographics were administered. Statistical analysis was conducted to assess associations between stigma and depression, stigma and QOL and stigma and race, while adjusting for demographic characteristics. Results Participants (N = 56) included 30 Caucasian and 26 African American survivors of lung cancer recruited from a cancer registry of an American College of Surgeons‐accredited programme, a survivors' support club and an ambulatory oncology practice in the southeastern United States. Statistical analysis yielded (1) a significant moderate positive association between depression and lung cancer stigma; (2) a significant moderate negative association between QOL and lung cancer stigma; and (3) significant relationships between race and lung cancer stigma, specifically higher degree of stigma among African Americans compared to Caucasians. Conclusion Stigma affects many aspects of survivors' lives. Healthcare professionals need to consider how health‐related stigma may further complicate the physical burdens, psychological distresses and social challenges that accompany the disease, especially among African American survivors. Additional enquiry and interventions are needed to assist with mitigating the negative effects of stigma on survivors and their family members and friends. Patient or Public Contribution Fifty‐six survivors of lung cancer participated in this descriptivecorrelation study. They completed written surveys measuring depression, QOL, and lung cancer stigma, plus an investigator‐developed demographic information form.